Subarrayed Antenna Array Synthesis Using Ternary Adjusting Method - Guolong He; Yafeng Zhan; Yukui Pei; Bin Wu (International Journal of Antennas and Propagation)
Ternary adjusting method is proposed and combined with particle swarm optimization (PSO) algorithm for subarrayed antenna array synthesis. Ternary variables are introduced to represent element adjustments between adjacent subarrays. Compared to previous methods, rounding-off operations are not required any longer, and the equation constraint of the fixed total element number is also removed, which effectively reduces the complexity of implementation while obtaining improved topology exploration capability simultaneously.